2019
DOI: 10.1097/nmd.0000000000001001
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abnormalities in Different Phases of Working Memory in Schizophrenia

Abstract: The current study aimed to examine both gray matter and functional activity changes in schizophrenia by combing both structural and task-related functional magnetic resonance imaging (fMRI). Nineteen patients with schizophrenia and 17 controls were recruited. The fMRI scan was performed while performing a working memory (WM) task. In terms of task performance, accuracy did not differ between groups, but there were significant differences in reaction time. Compared with controls, patients exhibited decreased fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In other studies stronger fMRI response in bilateral pre‐frontal cortex (PFC) including medial prefrontal cortex (MPFC), ACC, PCC, superior temporal cortex (STC), middle temporal cortex (MTC) and cuneus, and right occipital cortex and parahippocampus, and weaker fMRI response in bilateral DLPFC, right MPFC, insula, parietal cortex and ventral striatum and left posterior cerebellum, during performance of WM tasks by patients with SZ compared to HC have been reported (Glahn et al, 2005; Meyer‐Lindenberg et al, 2001; Van Snellenberg et al, 2016). In several studies, including a meta‐analysis (Van Snellenberg, Torres, & Thornton, 2006), a region of interest (ROI) analysis was performed specifically for DLPFC and found stronger fMRI response (Karlsgodt et al, 2009; Manoach et al, 2000; Potkin et al, 2009; Van Snellenberg et al, 2016), weaker fMRI response (Fan et al, 2019; Kaminski et al, 2020; Menon, Anagnoson, Mathalon, Glover, & Pfefferbaum, 2001; Pu et al, 2019) or no significant difference in fMRI response (Van Snellenberg et al, 2006) in patients with SZ compared to HC. Additionally, using independent component analysis (ICA), several fMRI studies of WM tasks have revealed significant alterations of fMRI response in patients with SZ relative to HC, which are either correlated or anti‐correlated with WM performance, including stronger fMRI response in bilateral superior frontal gyrus (SFG), PCC, insula, superior temporal gyrus (STG), inferior temporal gyrus, precuneus, parahippocampal gyrus, amygdala, putamen and cerebellum, left DLPFC, cingulate gyrus and inferior parietal lobule (IPL) (Chatterjee et al, 2019; Kim et al, 2009), and weaker fMRI response in bilateral dentate gyrus and cerebellum (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies stronger fMRI response in bilateral pre‐frontal cortex (PFC) including medial prefrontal cortex (MPFC), ACC, PCC, superior temporal cortex (STC), middle temporal cortex (MTC) and cuneus, and right occipital cortex and parahippocampus, and weaker fMRI response in bilateral DLPFC, right MPFC, insula, parietal cortex and ventral striatum and left posterior cerebellum, during performance of WM tasks by patients with SZ compared to HC have been reported (Glahn et al, 2005; Meyer‐Lindenberg et al, 2001; Van Snellenberg et al, 2016). In several studies, including a meta‐analysis (Van Snellenberg, Torres, & Thornton, 2006), a region of interest (ROI) analysis was performed specifically for DLPFC and found stronger fMRI response (Karlsgodt et al, 2009; Manoach et al, 2000; Potkin et al, 2009; Van Snellenberg et al, 2016), weaker fMRI response (Fan et al, 2019; Kaminski et al, 2020; Menon, Anagnoson, Mathalon, Glover, & Pfefferbaum, 2001; Pu et al, 2019) or no significant difference in fMRI response (Van Snellenberg et al, 2006) in patients with SZ compared to HC. Additionally, using independent component analysis (ICA), several fMRI studies of WM tasks have revealed significant alterations of fMRI response in patients with SZ relative to HC, which are either correlated or anti‐correlated with WM performance, including stronger fMRI response in bilateral superior frontal gyrus (SFG), PCC, insula, superior temporal gyrus (STG), inferior temporal gyrus, precuneus, parahippocampal gyrus, amygdala, putamen and cerebellum, left DLPFC, cingulate gyrus and inferior parietal lobule (IPL) (Chatterjee et al, 2019; Kim et al, 2009), and weaker fMRI response in bilateral dentate gyrus and cerebellum (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the FC between BNAcc and LING was higher in both DS and NDS patients. The LING, which is located in the medial occipital lobe, is involved in visual processing and several cognitive functions ( 35 , 36 ). A previous longitudinal study reported a significant increase of gray matter volumes within the bilateral lingual gyrus in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the lingual gyrus and lateral temporal lobes participate in and maintain working memory processing ( Zamora et al, 2016 ; Moon and Jeong, 2017 ; Fan et al, 2019 ). A study on a similar diabetic population also reported an association between poor working memory in patients and disrupted connectivity of the occipital network anchored in the lingual gyrus ( Cui et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the consistent results of structural and functional studies, we believe that altered cerebellum-cerebral ECN is mainly manifested in cross-projecting functional abnormalities in T2DM. Several studies have found that the lingual gyrus and lateral temporal lobes participate in and maintain working memory processing (Zamora et al, 2016;Moon and Jeong, 2017;Fan et al, 2019). A study on a similar diabetic population also reported an association between poor working memory in patients and disrupted connectivity of the occipital network anchored in the lingual gyrus (Cui et al, 2016).…”
Section: Decreased Connectivity Of the Cerebellum-cerebral Ecn In T2dmmentioning
confidence: 97%